2019
DOI: 10.1002/mmce.21863
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterial‐inspired miniaturized antenna loaded with IDC and meander line inductor using partial ground plane

Abstract: In this article, a novel omnidirectional compact dual band metamaterial‐inspired antenna with CPW feed has been proposed for application of GSM 1800 (1.71‐1.785 GHz/1.805‐1.879 GHz), GSM 1900 (1.85‐1.91 GHz/1.93‐1.99 GHz), UMTS (1.92‐2.17 GHz), WLAN/Wi Fi (4.9, 5, 5.9 GHz), HiperLAN1 (5.15‐5.3 GHz), and HiperLAN2 (5.47‐5.72 GHz) using a combination of meander line inductor and interdigital capacitor (IDC). The antenna consists of complimentary right/left handed (CRLH) transmission line on both sides of patch t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Although electrical size of suggested antenna is slightly larger than References 15 and 16 according to Table 2, but size reduction can be achieved by reducing the width ( w 1 ) of meander line turns. In addition, peak gain of suggested antenna at ZOR frequency is lower than References 19, 21, and 22 because overall size these antennas are greater than suggested antenna. Also antennas given in References 19 and 21 are planar structure antennas same as suggested but antenna in Reference 22 having complicated structure from fabrication point of view.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Although electrical size of suggested antenna is slightly larger than References 15 and 16 according to Table 2, but size reduction can be achieved by reducing the width ( w 1 ) of meander line turns. In addition, peak gain of suggested antenna at ZOR frequency is lower than References 19, 21, and 22 because overall size these antennas are greater than suggested antenna. Also antennas given in References 19 and 21 are planar structure antennas same as suggested but antenna in Reference 22 having complicated structure from fabrication point of view.…”
Section: Resultsmentioning
confidence: 82%
“…In addition, peak gain of suggested antenna at ZOR frequency is lower than References 19, 21, and 22 because overall size these antennas are greater than suggested antenna. Also antennas given in References 19 and 21 are planar structure antennas same as suggested but antenna in Reference 22 having complicated structure from fabrication point of view.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In 2014, DadGarpour showed that by placing a metamaterial lens layer in front of an antenna structure called a bow tie antenna, the antenna main beam could be directed in a desired direction and accordingly the antenna performance could be improved (Dadgarpour et al, 2014). In addition to these studies, there are also several antenna studies using MM (Kumar A and Kumar VD, 2013;Rahman et al, 2018;Arayeshnia et al, 2019;Singh HS et al, 2019;Singh M, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the ZOR has narrowband property and hence is not preferred in many designs. Due to this bandwidth enhancement of the metamaterial antenna is one of the popular research topics . Metamaterial antennas can also be realized by epsilon negative transmission line (ENG‐TL) .…”
Section: Introductionmentioning
confidence: 99%